Characterization of nontyphoidal Salmonella strains from a tertiary hospital in China: serotype diversity, multidrug resistance, and genetic insights - Ma, Wanshan; Cui, Xiaodi; Dong, Xiutao; Li, Xinpeng; Liu, Ke; Wang, Yujiao; Shi, Xiaohong; Chen, Liang; Hao, Mingju (Frontiers in Cellular and Infection Microbiology, 2024)
Objective: Nontyphoidal Salmonella is a significant public health concern due to its ability to cause foodborne illnesses worldwide. This study aims to characterize the nontyphoidal Salmonella strains isolated from patients in China.Methods: A total of 19 nontyphoidal Salmonella strains were characterized through serovar identification, antimicrobial susceptibility testing (AST), biofilm formation assessment. Genetic relatedness was determined using pulsed-field gel electrophoresis (PFGE). WGS was employed to decipher the resistance mechanism and to contextualize the S. serovar Mbandaka strains among previously sequenced isolates in China. The biofilm associated mrkA gene was examined by PCR.The predominant serovar identified was S.